Risk Assessment of Heavy Metal Accumulation in Leafy Vegetables Around Wastewater-irrigated Areas - Rahman, Tawfeequa; Mostafa, M.G. (Journal of Sustainability and Environmental Management, 2024)
The consumption of heavy metal-contaminated vegetables poses a threat to human health and the environment. This study assessed the level of heavy metals in selected leafy vegetables collected from wastewater-irrigated agricultural land located at Jalkuri Union of Siddhirganj Upazila in Narayanganj district of Bangladesh. The mean concentrations of metals were decreasing in the following order: Fe > Mn > Zn > Pb> Cr> Cu > Ni > Cd in wastewater, Fe> Mn > Cr > Zn > Ni > Pb> Cu> Cd in irrigated soil, and Fe > Zn > Mn> Cu> Pb > Cr> Ni > Cd in leafy vegetables. The contamination factor (CF) showed that the soils were moderate to highly contaminated by Cr and Cd. The pollution load index (PLI) and geo-accumulation index (Igeo) values of the analyzed samples revealed that the soils were non-polluted to moderately polluted. The target hazard quotients (THQ) for most of the metals were <1, suggesting non-carcinogenic health hazards for humans. The target carcinogenic risk (TCR) of heavy metals, except for Pb, was above the safe standard, suggesting a carcinogenic risk (CR) for their consumption. It is a matter of concern that regular intake of contaminated leafy vegetables in the area would increase health risk, as the hazard index (HI) was greater than 1. The study observed that vegetables should not be irrigated with contaminated water, and industrial wastewater must be properly treated before discharging into the environment.